Elementary School Students' Mathematical Creative Thinking Ability - Herman Syafri (Universitas Pendidikan Indonesia (UPI), 2023)
Mathematical creative thinking is required to develop analytical, evaluative, problem-solving, and critical information connection abilities. Elementary school students will have a strong foundation for studying mathematics at a higher level and for facing daily challenges if they are encouraged to think creatively in mathematics. The present study aimed to determine the profile of elementary school student's ability to think creatively in mathematics. This study employed a quantitative descriptive survey with a sample size of 48 elementary school pupils aged 7 to 12. The instrument used was a 32-question test of mathematical creative thinking with a maximum score of 40 and three dimensions, namely fluency, variability, and novelty, with a 0.86 level of reliability. The results indicate that the average value of mathematical creative thinking in the